The dynamics of oppression portrayed in Harold Pinter's One for the Road and Salah Abdul-Saboor's Night Traveller - Zohdi, Salma (AUC Knowledge Fountain, 2012)
This thesis comparatively analyzes the dynamics of oppression portrayed in Harold Pinter's One for the Road, and Salah Abdul-Saboor's Night Traveller, using Augusto Boal's Theatre of the Oppressed, Frantz Fanon's The Wretched of the Earth, and â Theater of the Absurdâ for the critical framework. With oppressive regimes regenerating themselves, and morphing into new types of practices, the power of art remains an essential motivation for the masses to resist those regimes. This applies particularly to theater, due its vitality. Whilst one may utilize a theatrical performance to entertain, others may utilize it to either inspire resistance, or chronicle and criticize a community's state. With works like One for the Road and Night Traveller that chronicle oppression through a theatrical political platform, oppressed audience members could be inspired to resort to resistance rather than to submission, and become empowered to be part of a positive change. My thesis argues that these two plays are necessarily oppressive, with an intense oppressor-oppressed dynamic, where the former exerts all available resources to silence the latter. However if both plays are performed to oppressed subjects in a â Theater of the Oppressedâ technique, they may function as an empowering tool of resistance.